MoS2/ZnO nanocomposites for efficient photocatalytic degradation of industrial pollutants. (March 2019) - Krishnan, Unni; Kaur, Manjot; Kaur, Gurpreet; Singh, Kulwinder; Dogra, Ankit Rai; Kumar, Manjeet; Kumar, Akshay
Graphical abstract: Highlights: MoS2 /ZnO nanocomposite for photocatalysis. Catalysis of Novacron red Huntsman (NRH) and methylene blue (MB) dye. Degradation mechanism of industrial pollutants. Abstract: In the present work, molybdenum disulphide-zinc oxide (MoS2 /ZnO) nanocomposites were synthesized via a simple dual step hydrothermal reduction method using hydrazine hydrate as a reducing agent. The as prepared nanocomposites have been characterized by X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), Raman and photoluminescence (PL) spectroscopy. The structural and morphological analysis showed that particles are crystalline in nature and cubical in shape with an average size of ∼22.5 nm.The nanocomposites were evaluated for photocatalytic property. The degradation analysis of industrial pollutants such as Novacron red Hunts- man (NRH) and methylene blue (MB) dye reveals that MoS2 /ZnO nanocomposite is an efficient catalyst.